2019
DOI: 10.36415/dagcilik.644204
|View full text |Cite
|
Sign up to set email alerts
|

Beden Eğitimi ve Spor Dersine Yönelik Ortaokul Öğrencilerinin Değer Düzeylerinin İncelenmesi (Bağcılar İlçesi Örneği)

Abstract: Milli kültür ve beraberlik (X̄= 4,025), Farkındalık (X̄= 4,644) düzeyleri yüksek olduğu belirlenmiştir. Cinsiyet değişkeninde; farkındalık alt boyutunda kızlar lehine anlamlı bir fark ortaya çıkarken, spor yapma durumlarında spor yapan öğrenciler lehine anlamlı düzeyde bir fark bulunmuştur. Sınıf düzeyi değişkenine göre beden eğitimi dersi değer düzeylerine bakıldığında; Spor kültürü, Sağlıklı yaşam ve beslenme, Dayanışma, Saygı, Milli kültür ve beraberlik boyutlarında anlamlı düzeyde farklar olduğu ortaya çı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…The values levels of the students can be listed in descending order as; awareness, respect, solidarity, healthy life and nutrition, sports culture, and national culture and unity. The study conducted by Sağın and Karabulut (2019), similarly found that the values scores of secondary school students for physical education lessons were high. In the study conducted by Işıkgöz, Esentaş and Işıkgöz (2018), it was seen that students studying at secondary school exhibited the highest level of values for physical education and sports lesson in the "awareness" dimension and the lowest level value was "National Culture and Unity".…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 89%
See 1 more Smart Citation
“…The values levels of the students can be listed in descending order as; awareness, respect, solidarity, healthy life and nutrition, sports culture, and national culture and unity. The study conducted by Sağın and Karabulut (2019), similarly found that the values scores of secondary school students for physical education lessons were high. In the study conducted by Işıkgöz, Esentaş and Işıkgöz (2018), it was seen that students studying at secondary school exhibited the highest level of values for physical education and sports lesson in the "awareness" dimension and the lowest level value was "National Culture and Unity".…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 89%
“…It is also stated that the qualities that instill children to be good people and that they need to be in order to become respected members of the society with basic root values, can be provided by physical education and sports activities (Dunn, Kinney and Hofferth, 2003). It is stated in the curriculum of the physical education and sports education course that physical education and sports activities, which are accepted as an activity area where students make sports a lifestyle and aim the development of students physically and mentally from the past to the present and to the future, are the values that skills, knowledge, attitudes and basic values should be transferred and be gained by students through these activities (Sağın and Karabulut, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is quite interesting and disheartening to observe that a class that is so much favored and loved by students and adults including educators (Balga, Antala, & Argajová, 2019;Çelik, Koçkaya & Parlar, 2018;Demir, Cicioğlu, İlhan, & Arslan, 2017;Graham, 2008;Mohammed & Mohammad, 2012;Pehlivan, Dönmez & Yaşat, 2005;Sağın and Karabulut (2019;Tutal, 2014) is largely marginalized and undermined. As articulated by participants in this study, it appears that much talk by stakeholders at schools on this course does not go beyond rhetoric and what happens in practice is a complete opposite.…”
Section: Discussion a N D Conclusionmentioning
confidence: 99%
“…A study conducted by Çelik, Koçkaya and Parlar (2018) with 402 students revealed that most students have quite positive attitudes towards this class. Sağın and Karabulut (2019) also found out that the level of value students place on various dimension of PE course are high. What is more, although comparably at lower levels, teacher candidates (Demir, Cicioğlu, İlhan, & Arslan, 2017), teachers (Pehlivan, Dönmez & Yaşat (2005), and school administrators (Tutal, 2014) also rate it as a valuable course.…”
Section: Introductionmentioning
confidence: 89%
“…Bu araç nicel verilerin elde edilmesinde kullanılır (Cresswell ve Plano Clark, 2018). Beden Eğitimi ve Spor Dersi Lise Değer Ölçeği'nin (BESDLDÖ) Geliştirilmesi Birinci aşamada değerler eğitimi ile ilgili literatür taraması yapılarak benzer nitelikteki çalışmalar ve ölçekler incelenmiştir (Berkowitz, 2011;Kangalgil vd., 2021;Sağın ve Karabulut, 2019;Yıldız ve Güven, 2013;Yücekaya, 2017). Ardından BES değerlerine ilişkin 3 öğretim üyesi, 6 BES öğretmeni ve 30 lise öğrencisi ile BES dersi ile ilgili "yarı yapılandırılmış görüşme formu" ile karşılıklı görüşmeler yapılmıştır.…”
Section: Yöntem Araştırma Modeliunclassified